2015
DOI: 10.3109/1354750x.2015.1068853
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 levels correlate with poor prognosis and vascular endothelial growth factor concentration in the serum of patients with non-small cell lung cancer

Abstract: IL-17 may play a role in NSCLC progression by promoting angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 42 publications
4
28
1
Order By: Relevance
“…These data were supported by work showing IL-17A to facilitate angiogenesis in lung cancer cell lines [55], and high circulating levels of IL-17 in NSCLC patients to be an independent bad prognostic factor [56]. A similar study by Yu and colleagues confirmed that serum levels of IL-17 are elevated and can be used as an independent prognostic factor in NSCLC [57].…”
Section: Il-17 Prognostic and Predictive Value In Lung Cancersupporting
confidence: 62%
“…These data were supported by work showing IL-17A to facilitate angiogenesis in lung cancer cell lines [55], and high circulating levels of IL-17 in NSCLC patients to be an independent bad prognostic factor [56]. A similar study by Yu and colleagues confirmed that serum levels of IL-17 are elevated and can be used as an independent prognostic factor in NSCLC [57].…”
Section: Il-17 Prognostic and Predictive Value In Lung Cancersupporting
confidence: 62%
“…Cigarette smoking which is associated with over 80% of all lung cancers, recruits Th17 cells in the lungs (13,14), and has been associated with poor survival in NSCLC patients (15). Serum IL17A level is positively linked to vascular endothelial growth factor (VEGF) concentration in NSCLC patients, suggesting IL17A may promote angiogenesis in the tumor (16). Further, patients with high serum IL17A concentrations demonstrated a shorter overall survival rate compared with those with low levels (17).…”
Section: Pro-tumor Effect Of Il17amentioning
confidence: 99%
“…10 The presence of IL-17 and IL-17-expressing cells has recently been studied in several types of cancer, including NSCLC. [11][12][13][14][15][16] High serum IL-17 levels were detected in NSCLC patients and were significantly correlated with a late stage of NSCLC, overall survival (OS), and disease-free survival (DFS). [13][14][15] IL-17 in human NSCLC tissues was also significantly elevated and high IL-17 expression was significantly correlated with the clinical and pathological features of patients, such as TNM staging, OS and DFS.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] High serum IL-17 levels were detected in NSCLC patients and were significantly correlated with a late stage of NSCLC, overall survival (OS), and disease-free survival (DFS). [13][14][15] IL-17 in human NSCLC tissues was also significantly elevated and high IL-17 expression was significantly correlated with the clinical and pathological features of patients, such as TNM staging, OS and DFS. 11,12 In addition, the frequencies of IL-17-producing T cells (IL-17 + CD4 + Th17, IL-17 + CD8 + Tc17, and IL-17A + γδT17 cells) have been found to be dysregulated in NSCLS patients.…”
Section: Introductionmentioning
confidence: 99%